2018
DOI: 10.1093/hropen/hoy020
|View full text |Cite
|
Sign up to set email alerts
|

MED12 mutations and fumarate hydratase inactivation in uterine adenomyomas

Abstract: STUDY QUESTION Do the uterine leiomyoma driver events – mediator complex subunit 12 ( MED12 ) mutations, high mobility group AT-hook (HMGA2) overexpression, and fumarate hydratase (FH) inactivation – also contribute to the development of uterine adenomyomas? SUMMARY ANSWER MED12 mutations and FH deficiency occur in a subset of uterine adenomyomas, but at lower frequencies than in leiomyomas. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Mutation screening revealed FH mutations in 8 out of 11 tumours. Four of the mutations have been reported earlier (Heikkinen et al, 2018;Kiuru et al, 2002;Bayley et al, 2008), and in silico predictions for the novel variants indicated three of them to be pathogenic (Kopanos et al, 2019). Limitations of the direct sequencing method in recognizing large deletions, insertions, or changes in the regulatory regions probably explain why a mutation was not identified in the remaining three samples.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Mutation screening revealed FH mutations in 8 out of 11 tumours. Four of the mutations have been reported earlier (Heikkinen et al, 2018;Kiuru et al, 2002;Bayley et al, 2008), and in silico predictions for the novel variants indicated three of them to be pathogenic (Kopanos et al, 2019). Limitations of the direct sequencing method in recognizing large deletions, insertions, or changes in the regulatory regions probably explain why a mutation was not identified in the remaining three samples.…”
Section: Discussionmentioning
confidence: 84%
“…MED12 mutations lead to the uncoupling of Cyclin C and CDK8/19 from the core Mediator, loss of Mediator associated CDK kinase activity, and a unique global gene expression pattern (Mehine et al, 2013;Turunen et al, 2014;Kämpjärvi et al, 2014). In addition to uterine leiomyomas, MED12 mutations have been reported in other female hormone-dependent tumours such as breast fibroadenomas (Chang et al, 2020), phyllodes tumours, and uterine adenomyomas (Heikkinen et al, 2018). Roughly 10% of leiomyomas show high mobility group AT-hook 2 (HMGA2) overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that DNA mutations in uterine smooth muscle tumors are also found in a subgroup of UAs and that driver mutations contribute to the development of some adenomyomas; however, the pathogenesis may be different, and large-scale genomic analyses are needed to elucidate the complete molecular background of UAs. [12] The diagnosis of UA still requires histopathological examination, in which endometrial glands and mesenchyme are seen microscopically in an insular distribution in the myometrium, and the basal layer of ectopic endometrium usually forms a complex structure of horizontally interconnected glands, which is different from the glands in functional endometrium, which are isolated, unbranched, and longitudinally arranged. However, the gold standard for the histopathologic definition is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNA mutations in uterine smooth muscle tumors are also found in a subgroup of UAs and that driver mutations contribute to the development of some adenomyomas; however, the pathogenesis may be different, and large-scale genomic analyses are needed to elucidate the complete molecular background of UAs. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations of the MED12 gene are detected in 70%-75% of patients with LM [26,27] and arise de novo directly in myoblasts. In addition to LM cells, MED12 gene mutations also occur in adenomyosis (internal endometriosis) [28] and in mammary adenomyoma cells [25]. When mutations of the MED12 gene occur in ontogeny remains unknown.…”
Section: Tumor Initiationmentioning
confidence: 99%